P ERANAN TUTOR SEBAYA DALAM MEMBANTU PROSES PEMBELAJARAN BAGI SISWA TUNARUNGU DI SMP N 23 PADANG - Selvi, Mega Iswari, Ardisal (Jurnal Penelitian Pendidikan Khusus, 2013)
The background of this research is deaf student’s have difficulty in following the learning process in the classroom especially in children of class VIII. The research was conducted at SMP 23 Padang,and purpose of this research is to see how far  role of peer tutors in assisting the process of learning for deaf students. The methodology of this research is descriptive qualitative approach. The study subjects consisted of three deaf students at Junior High School 23 Padang. Techniques of collecting data through observation, interviews, and documentation. The result of this research is divided into two. Namely general findings and specific findings. General findings are only limited peer tutors provide assistance to children with hearing impairment when there are obstacles to learning, however, is a specific finding there are obstacles in the role of peer tutors help students with visual impairment due to peer tutors in learning and the school sometimes less actually provide services to children with hearing because do not really understand the services to be rendered real